The mediating role of marriage horizon components in the relationship between attachment styles and attitudes toward marriage - Dayani Dardashti, Hori; Zarbakhsh, Mohammad Reza; Manzari Tavakoli, Reza (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Recently the study of factors affecting young people's attitudes toward marriage has a special place. The aim of this study was to determine the mediating role of marriage horizon components in the relationship between attachment styles and attitudes toward marriage. Method: This study was a descriptive-correlational. The study population consisted of single girls in Isfahan, who during a call in cyberspace according to the purpose of the study, 265 people announced their readiness, and then the link to the Collins and Reed (1990) Adult Attachment Styles Questionnaire, Attitudes and Expectations of Marriage Bratton And Rosen (2012), The Importance of Marriage Belt (2016), The Expected Marriage Age of Willoughby (2014), and The Marriage Preparation of Johnson, Anderson, & Stath (2011) Correlation and path analysis were analyzed with AMOS24 and SPSS26 software. Results: The model of structural equations of the research had a good fit. The results showed that secure attachment style (β = -0.231, P